Challenges to the use of fertilisers derived from human excreta: The case of vegetable exports from Kenya to Europe and influence of certification systems - Moya, Berta; Parker, Alison; Sakrabani, Ruben (Elsevier, 2019)
Land degradation and inadequate faecal sludge management are two major issues in Sub-Saharan Africa (SSA). The transformation of human excreta into soil amendments and their wide-scale adoption could improve soil health and contribute to solving the sanitation crisis in SSA. There are however perception challenges around these fertilisers because of the potentially harmful components they contain such as pathogens and heavy metals, which can be removed with appropriate treatment such as composting. A major barrier to the wide scale commercialisation of human excreta derived fertiliser (HEDF) is the unclear regulations surrounding their use. The aim of this study was to identify barriers to the use of HEDF by farmers participating in the horticultural export market with Kenya as focus area since horticultural exports are a major contributor to the country’s economy. Global GAP is the most widely adopted standard for quality assurance of horticultural crops and the use of human sewage sludge is currently not allowed on certified farms. Interviews with stakeholders along the food export chain highlighted the complex interactions that exist between them and showed that Global GAP certified farmers were not willing to use HEDF on their farms even if local regulations recognise treated sludge as a valid input to agriculture. Several countries (like the UK, Sweden, Australia and the USA) created specific certification or assurance schemes to improve public perception of biosolids. The creation of a similar assurance or certification scheme specific to fertilisers made from source-separated human excreta would be a step into formalising them as a product, establishing production procedures, limits on contaminants content as well as testing protocols. Such a certification scheme could increase the confidence of regulating bodies in HEDF and lead to their acceptance by global farming standards.
Keywords: Compost; Sludge; Human excreta; Fertiliser; Export; Certification